Pengaruh Return On Equity, Deb To Equity Ratio dan Current Ratio terhadap Harga Saham Perusahaan yang terdaftar di Jakarta Islamic Indeks dengan Price Earning Ratio sebagai Variabel Moderating - Nur Ahmadi Bi Rahmani (Universitas Islam Negeri Sumatera Utara, 2020)
Capital markets provide opportunities for people to participate in the development of an economy. With the capital market, companies can more easily get capital from the community so as to create broad jobs and increase taxes for the government. The capital market as an instrument is not separated from various influences, especially the economic environment. The influence of the microeconomic environment for example the performance of the company can be seen from the financial ratios of the company. The purpose of this study is to analyze the effect of return on equity, deb to equity ratio and current ratio on the share price of companies listed in jakarta islamic index with price earning ratio as variable moderating. The population and samples used were jii-registered companies from 2015 to 2019. The results show that by using a significant rate of five percent, roe variables have a significant influence on the share price, DER variables have a significant influence on the share price, CR variables have a significant influence on the share price, PER variables can significantly strengthen the influence of roe variables on the company's share price, PER variables can significantly strengthen the influence of DER variables on the company's share price , and per variables can significantly strengthen cr's influence on the company's share price.